ORBIT - Jay Apt, Michael Helfert & Justin Wilkinson; Micheal Helfert; Justin Wilkinson (U.S.A National Geographic Society, 1996)
To show the range of Earth's geology and climate, each section highlights the major geological features found in each region and if appropriate mankind's influence.